"StatLit: tactical interventions for strategic transformation". Issue 9 (6th November 2017) - Porter, Seth; Doshi, Ameet
Abstract : Purpose: This paper was inspired by an Association of College and Research Libraries Biennial Conference 2017 roundtable that aimed to transform existing notions about statistical literacy in information literacy instruction. Design/methodology/approach: In Baltimore, the authors facilitated an in-person discussion and synchronous virtual dialogue via Twitter and Periscope about teaching basic statistical concepts (such as mean vs median) and the real implications of "statistical significance". Findings: A recording of the roundtable is available here: http://bit.ly/StatLit. Originality/value: The goal of the StatLit roundtable was to inspire transformational thinking for teaching basic statistical reasoning to students within a library context.